New Method of 2-Arylbenzoxazole Synthesis from 2-Aminophenol Derivatives and Benzaldehyde Using Sulfur as an Oxidant - Nguyen, Le Anh; Dang, Thai Duy; Nguyen, Thanh Binh; Ngo, Quoc Anh (JST: Engineering And Technology For Sustainable Development, 2021)
In previous studies, the synthesis of 2-arylbenzoxazole derivatives required strongly acidic conditions, prolonged heating at high temperatures and significant amounts of expensive/toxic transition metal catalysts. A major drawback of using oxygen as an oxidant is the risk of explosion of flammable organic substrates. Moreover, due to its gaseous state, exact stoichiometric control of oxygen amounts used in the reaction is not readily possible. Therefore, new methods of mellow conditions with eco-friendly agents is targeted by our team. In this study, sulfur (S8) is found as an effective oxidizer in the oxidation reaction condensation between 2-aminophenols with benzaldehydes to obtain different 2-arylbenzoxazole. In the presence of Na2S as catalysts and DMSO as an additive the reactions give good yield in only one step at the ambient temperature.